Implementasi Teknologi ERP Modul Human Resource Management Pada Satuan Polisi Pamong Praja Kotawaringin Timur - Bayu Nur Rohman; Lukman Bachtiar (Journal of Computer System and Informatics (JoSYC), 2020)
Along with the development of increasingly sophisticated technology and information, the human need for information technology is also getting bigger. The development of information technology can improve performance and enable various activities to be carried out quickly and accurately. Based on the development of information and communication technology, many companies have implemented Enterprise Resources Planning (ERP). The Civil Service Police Unit Service is an apparatus of the Regional Government in enforcing Regional Regulations. In an activity or assignment at the civil service police unit, a Task Order (SPT) is required. In addition, the assignment letter is a reference for calculating the crediting figures in an assessment of the promotion of a class of employees who have performed duties in several periods. The system that has been running so far is still done conventionally. Where archiving the entry and exit of letters, salary report data, leave reports and attendance reports is still inefficient and data storage for credit score assessment is less effective because it often creates obstacles in data storage. Therefore, it is necessary to create a system to facilitate filing of letters and handle the problem of storing data for calculating class promotion credit numbers and data on salary reports, leave reports and attendance reports at the Civil Service Police Unit. In building this application program, using PHP as a programming language media and MySQL is used as database management